KAJIAN MENGENAI INSPANNING VERBINTENIS DAN RESULTAAT VERBINTENIS DI BIDANG KEDOKTERAN BEDAH PLASTIK DENGAN TUJUAN ESTETIKA - Janetty, Janetty (PMIH Untag Semarang, 2022)
Developments in the field of science, especially in health and medical field, have made finding solutions for medical treatment not only for health but also for beauty and body aesthetics through plastic surgery. Plastic surgeries, also other surgeries, are declared as a failure if the patient dies, but in plastic surgery it is also declared as a failure if the result does not meet consumer expectations. If the results doesn’t meet the patient’s expectation on what was predicted in the initial planning stage and it does not lead to an improvement in appearances is also a failure. This study method is normative juridical with secondary data as the main data, namely library research with analytical and conceptual approach. The result of this study indicate that plastic surgery with aesthetic goals, in healthy patient conditions, is the result of agreement or verbintenis because it focuses on the final result in accordance with a special agreement at the beginning between the doctor and the patient, namely the existence of real results as expected. However, this engagement also includes inspanning verbintenis because the plastic surgeon requires maximum efforts according to his competency standards to the patient and the final result may not be as predicted at the beginning due to unexpected factors that can occur and affect the results. The conclusion is that plastic surgery belongs to both, including inspanning verbintenis and resultaat verbintenis. The responsibility of plastic surgeons in inspanning verbintenis and resultaat verbintenis in the form of administrative, civil, and even criminal responsibilities. Therefore, in carrying out medical actions required seriousness and proper care so as not to cause harm to oneself and the patient.